Genistein Ameliorates Renal Fibrosis Through Regulation Snail via m6A RNA Demethylase ALKBH5 - Ning, Yichun; Chen, Jing; Shi, Yiqin; Song, Nana; Yu, Xiaofang; Fang, Yi; Ding, Xiaoqiang (Frontiers in Pharmacology, 2020)
Renal tubule-interstitial fibrosis is related to chronic kidney disease progression and a typical feature of the aging kidney. Epigenetic modifications of fibrosis-prone genes regulate the development of renal fibrosis. As a kind of “epigenetic diet”, soy isoflavone genistein was reported to have renal protective action and epigenetic-modulating effects. However, its renal protection role and underlying mechanisms are yet to be fully clarified. Herein, we showed that genistein exhibits a demonstrable anti-fibrotic effect on kidney in vivo UUO (unilateral ureteral occlusion) model and renal epithelial cells in vitro model. The mechanism is strongly associated with epithelial-to-mesenchymal transition and m6A RNA demethylase ALKBH5. Mouse fibrotic kidneys induced by UUO exhibited adverse expression of renal fibrosis-related proteins and significant increases in the total m6A level. As an eraser, ALKBH5 showed severer suppression in the renal fibrosis process. However, genistein pretreatment restored ALKBH5 loss remarkably and reduced renal fibrosis, abnormal protein, and inflammatory markers. The examination of possible mechanisms revealed that genistein promoted ALKBH5 and maybe induced the level of mRNA m6A methylation in some epithelial-to-mesenchymal transition-related transcription factors. We found snail was the critical regulator and critical for the protective role of genistein. To verify the relationship between ALKBH5 and snail, we generated knockdown and overexpression of ALKBH5 cells in vitro. ALKBH5 knockdown enhanced the mesenchymal phenotype marker α-smooth muscle actin and snail expression. In agreement, overexpression ALKBH5 increased epithelial adhesion molecule E-cadherin and reduced snail expression. In conclusion, genistein increased renal ALKBH5 expression in UUO-induced renal fibrosis and reduced RNA m6A levels and ameliorates renal damages.